2014
DOI: 10.18632/oncotarget.2066
|View full text |Cite
|
Sign up to set email alerts
|

Engineered ubiquitin ligase PTB-U-box targets insulin/insulin-like growth factor receptor for degradation and coordinately inhibits cancer malignancy

Abstract: The type 1 insulin-like growth factor receptor (IGF-1R) is a promising target for cancer therapy with antibodies and small molecule tyrosine kinase inhibitors (TKIs) which have been actively tested clinically. Evidences have demonstrated that insulin receptor (IR), which is implicated in tumorigenesis, conveys resistance to IGF-1R targeted therapy. This provided the compelling rationale for co-targeting IGF-1R and IR. Herein we have developed an approach to simultaneously down-regulate IGF-1R and IR in protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The activation of Akt induced by insulin accelerates the translocation of GLUT4 vesicles to the plasma membrane, which results in enhanced glucose uptake in the adipose and muscle cells (Gonzalez and McGraw, 2006). Notably, it has been reported that GLUT4 translocation into plasma membrane promotes hepatic glucose uptake, and insulin treatment promoted the translocation of GLUT4 in HepG2 cells (Wang et al, 2014). Our results showed that GLUT4 migration from cytosol to membrane induced by insulin was prevented by PA treatment.…”
Section: Discussionsupporting
confidence: 47%
“…The activation of Akt induced by insulin accelerates the translocation of GLUT4 vesicles to the plasma membrane, which results in enhanced glucose uptake in the adipose and muscle cells (Gonzalez and McGraw, 2006). Notably, it has been reported that GLUT4 translocation into plasma membrane promotes hepatic glucose uptake, and insulin treatment promoted the translocation of GLUT4 in HepG2 cells (Wang et al, 2014). Our results showed that GLUT4 migration from cytosol to membrane induced by insulin was prevented by PA treatment.…”
Section: Discussionsupporting
confidence: 47%
“…Another approach is to create a non-endogenous, chimeric E3 ubiquitin ligase that can specifically target the proteins of interest, by replacing the “recognizing and binding” region of an endogenous E3 by an adaptor molecule or directly fusing an E3 “catalytic” domain with an interacting domain of a specific adaptor. With these chimeric E3s, we and others successfully rewired the oncoproteins such as Myc 49 , KRAS 50 , HER2 32 42 , EGFR 33 42 , and IR/IGF-1R 34 to ubiquitin-proteasome degradation route, and as a result, the oncogenes-related malignant behaviors of tumor cells as well as in vivo tumor growth were remarkably inhibited. These promising results prompted us to test whether such a protein knockout strategy could be applied to targeted degradation of the wild type and mutant BCR-ABL in CML.…”
Section: Discussionmentioning
confidence: 99%
“…The U-box protein CHIP (carboxy terminus of Hsc70 interacting protein) can bind to the molecular chaperone Hsc70 and Hsp90 and mediates ubiquitination and subsequent degradation of their client proteins 31 . Previously, we successfully generated several chimeric ubiquitin ligases by fusing RING domain of Cbl or U-box domain of CHIP with a protein-protein interaction domain to specifically target the oncoproteins such as HER2 32 , EGFR 33 and IR/IGF-1R 34 , and we also demonstrated that they could effectively inhibited these oncoproteins-related tumors.…”
mentioning
confidence: 97%
“…More recent data have shown that an engineered ubiquitin ligase PTBU-box can promote the ubiquitination and degradation of IGF-IR and IR, and thus effectively inhibit in vitro and in vivo tumorigenesis of liver cancer HepG2 and cervical cancer HeLa cells that over-express IGF-IR and IR ( 39 ).…”
Section: Igf-ir Ubiquitination Endocytosis and Traffickingmentioning
confidence: 99%
“…Because different ubiquitin ligase proteins have been implicated in mediating the ubiquitination of the IGF-IR ( 28 , 33 , 37 , 39 ) we can speculate that different complexes may have different abilities in promoting either polyubiquitination or multiubiquitination of the receptor depending on either cell background or tumor model thus differentially affecting receptor sorting, stability, and biological activity (Figure 1 ).…”
Section: Igf-ir Ubiquitination Endocytosis and Traffickingmentioning
confidence: 99%